Illness perceptions, adjustment to illness and depression in a palliative care population. (1st April 2011) - Price, A; Goodwin, L; Rayner, L; Shaw, E; Hansford, P; Sykes, N; Monroe, B; Higginson, I J; Hotopf, M; Lee, W
Abstract : Abstract: Context: Representations of illness have been studied in several populations but research is limited in palliative care. Objective: To describe illness representations in a population with advanced disease receiving palliative care; and to examine the relationship between illness perceptions, adaptive coping and depression. Methods: A cross-sectional survey of 301 consecutive eligible patients recruited from a palliative care service in South London, UK. Measures used included the Brief Illness Perception Questionnaire (Brief IPQ), the Mental Adjustment to Cancer Scale (MAC) and the PRIME-MD PHQ-9. Results: Scores were not normally distributed for the majority of the questions on the IPQ. The correlations found between items on the Brief IPQ were understandable in the context of advanced disease. MAC hopelessness-helplessness and fighting spirit were highly correlated with items on the brief IPQ in opposite directions. The Brief IPQ domains of consequences, identity, concern, personal control and emotion were associated with depression; a relationship which was not explained by adaptive coping. Seven causal attribution themes were identified: Don't know, personal responsibility, exposure, pathological process, intrinsic personal factors, chance/fate/luck and other. Both lung cancer diagnosis and gender were found to be independently associated with personal responsibility attribution. None of the attribution themes were associated with the presence of depression. Conclusions: Assessment of illness perceptions in palliative care is likely to yield important information about risk of depression and will help clinicians to personalise management of advanced disease.